Mengukur Peran Budaya Organisasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Pada PT Pelni (Persero) Cabang Makassar - Mustafa Gani; Nur Fachri (Jurnal Ilmiah Bongaya, 2024)
This study aims to determine the effect of organizational communication and organizational culture on employee performance at PT. Pelni (Persero) Makassar Branch. The data used is secondary data in the form of data collected from time to time sequentially with documentation techniques. The population is 35 employees at PT. Pelni (Persero) Makassar Branch, while the sample used in this writing uses a saturated sample technique. The data collection method is multiple linear regression analysis, classical assumption test and hypothesis testing using SPSS 26. The results of this study indicate that Organizational Communication has a positive and significant effect on Employee Performance and Organizational Culture has a positive and significant effect on Employee Performance